Radically human : how new technology is transforming business and shaping our future - Daugherty, Paul R.; Wilson, H. James (Ascent Audio, 2022)
Technology advances are making tech more . . . human, changing everything you thought you knew about innovation and strategy. In their groundbreaking book Human + Machine, Accenture technology leaders Paul Daugherty and H. James Wilson showed how leading organizations use the power of human-machine collaboration to transform their businesses and their bottom lines. Now those companies and other pioneers across industries are reshaping the very nature of innovation. In Radically Human, Daugherty and Wilson show this profound shift-how artificial intelligence is becoming less artificial and more intelligent. How, instead of data-hungry approaches to AI, innovators are pursuing data-efficient approaches that enable machines to learn as humans do. And how, instead of replacing workers with machines, they are unleashing human expertise to create human-centered AI. Leading companies use these fresh approaches to the basic building blocks of business-Intelligence, Data, Experience, Architecture, and Strategy (IDEAS)-to transform competition, optimize post-pandemic approaches to work and talent, and show the way toward a sustainable future. With compelling insights and fresh examples from a variety of industries, Radically Human will forever change the way you think about, practice, and win with innovation.